Magnetically separable mesoporous alginate polymer beads assist adequate removal of aqueous methylene blue over broad solution pH. (15th October 2021) - Hassan, Masud; Deb, Amal Kanti; Qi, Fangjie; Liu, Yanju; Du, Jianhua; Fahy, Adam; Ahsan, Md Ariful; Parikh, Sanjai J.; Naidu, Ravi
Abstract: Adsorption is a promising technology for removal of organic and inorganic contaminants from soil and water system. In this study, magnetically separable mesoporous polymeric beads (NiZnFe4 O4 -HNT@alg) were synthesised for efficient removal of methylene blue (MB, cationic dye) under broad solution pH (from pH 3.41 to pH 8.43). Alginate biopolymer were used to stabilize halloysite nanotubes (HNTs) and nickel zinc iron oxide nanoparticles (NiZnFe4 O4  < 100 nm). NiZnFe4 O4 was incorporated onto the polymer beads to generate the adsorbents' magnetic properties and catalytic degradability. The adsorbent (NiZnFe4 O4 -HNT@alg) have higher surface area (122.43 m 2 /g), suitable mesoporosity (~6.68 nm), larger pore volume (0.11 cm 3 /g), and abundance of active sites, enabling high adsorption capacity (264 mg/g) of MB. The abundance of hydroxyl, carboxyl, and siloxane groups enabled cationic dye sorption through ionic interaction. The removal efficiency of MB was ~99% under a wide solution pH range from 10 mg/L of MB, in which the adsorbent dose was 2 g/L. Both Langmuir (R 2  = 0.99; p < 0.001) and Freundlich (R 2  = 0.99; p < 0.001) isotherm models fitted well, whereas trends of kinetics model fitting are pseudo-second-order (R2 = 0.99) > intraparticle diffusion (R 2  = 0.93) > pseudo-first-order (R 2  = 0.87). Energy-dispersive X-ray spectroscopy (EDS) elemental mapping demonstrated that MB has a co-distribution with silicon, aluminium, and alginate carbon phase but is limited with iron and nickel, indicating HNTs and alginate polymer performed as sorption sites, whereas NiZnFe4 O4 performed as a catalyst. The presence (post-sorption) and absence (pre-sorption) of inorganic, total carbon or total organic carbon content at different solution pH, contact time, and initial concentration of MB demonstrated that the adsorbent act as a catalyst as well for degradation of MB. NiZnFe4 O4 -HNT@alg triggers efficient removal of MB with the assist of adsorption and catalytic degradation at broad solution pH. A comparison in removal of MB by various adsorbents including, biochars, clays, activated carbon, nanoparticles, polymers, nano composites, graphene oxides, carbon nanotubes, and polymer beads with the result of this study were performed, illustrating competitive sorption capacity of NiZnFe4 O4 -HNT@alg. Graphical abstract: Image 1 Highlights: The adsorbent was prepared from single route polymerization process. The mesoporous (∼2-18 nm) adsorbent enables to diffuse methylene blue (MB). The adsorbent could remove 99% of MB over a broad range of solution pH. Pore filling, hydrogen bonding, and diffusion play vital role for adsorption of MB. Nickel-zinc-iron oxide perform as a catalyst for degradation of MB.